Singing Steadfast Love and Faithfulness: The Messianic Significance of Psalm 89 - Ellison, Davy (Old Testament essays, 2024)
Psalm 89 is a study in complexity. Debate ensues concerning its unity, structure, genre and historical setting. Its literary setting causes disagreement, which is not helped by the pivotal role it plays in understanding the shape of the Psalter. Most disorientating, however, is the contradictory emotions—exultant praise gives way to deep lament. The questions raised by these contradictory emotions remain unanswered. In this article, it is suggested that Ps 89 is best understood as having messianic significance. The case is made by noting that the psalm employs theological themes which culminate in the messiah, is heavily based on 2 Sam 7, fails to resolve, holds an important position in the Psalter’s shape and clearly contributes to the development of messianic hope in its early interpretation. The messianic significance of Ps 89, I contend, is found in its singing the steadfast love and faithfulness of Yhwh despite the bleak circumstances to which it alludes.